Case report: Transarterial chemoembolization for nasal hemangiosarcoma in a dog - Kim, Keunho; Lim, Changgyu; Kim, Songyi; Lim, Hearang; Hyun, Sang-Hwan; Kang, Byeong-Teck; Chang, Dongwoo; Lee, Namsoon (Frontiers in Veterinary Science, 2025)
This report outlines the use of transarterial chemoembolization (TACE) to treat a nasal tumor in a 10-year-old Welsh Corgi. The dog initially presented with persistent nasal discharge and facial deformity, which led to a diagnosis of nasal hemangiosarcoma. Although initial treatments with radiotherapy and chemotherapy provided temporary relief, the symptoms reappeared 11 months later. As a palliative measure, TACE was administered, utilizing carboplatin as the chemotherapeutic agent and gel foam as the embolic material. The procedure successfully reduced the tumor size and alleviated the dog’s symptoms. Follow-up CT scans at 1, 3, 7, and 10 months, demonstrated sustained tumor shrinkage. Interestingly, there was no reperfusion of the embolized vessels, indicating a prolonged therapeutic effect. No significant complications were observed during follow-up. This case highlights the potential of TACE as a palliative option for managing recurrent nasal tumors in dogs, especially when other treatments have limited efficacy. Further research is needed to establish TACE guidelines for treating nasal tumors in veterinary medicine.